Effects of Different Activating Agent on the Physicochemical Properties of Rice Husk Derived Graphene (GRHA). Issue 1 (December 2020) - Arifin, N F T; Yusof, N; Nordin, N A H M; Jaafar, J; Ismail, A F; Aziz, F; Salleh, W N W
Abstract: This paper proposes the preparation of rice husk derived graphene (GRHA) via chemical activation method using two different chemical activating agents namely phosphoric acid (H3 PO4 ) and potassium hydroxide (KOH). The purpose of this study is to study the impact of different activating agent on the physicochemical properties of GRHA. The rice husk was carbonized at 350 °C for 2 h and activated at 900 °C and 700 °C for GRHA-KOH and GRHA-H3 PO4 respectively. The prepared GRHA was characterized using X-ray Diffraction (XRD) analysis, Raman Spectroscopy and BET analysis. The crystallinity of each sample shows that the prepared GRHA is in amorphous state. On the other hand, the ID /IG ratio of GRHA-KOH is 0.45 while GRHA-H3 PO4 is 0.68 which suggest that both samples have high degree of graphitization. Interestingly, it was discovered that activation using KOH possesses a higher BET specific surface area (BETSSA ), 518.11 m 2 /g as compared to H3 PO4 which is only 315.07 m 2 /g. Thus, it shows that KOH was able to form GRHA with higher surface area and porosity.